The role of cub scout extracurricular in student character building: Analysis and implications - Noval, Ardin; Sulistyarini, Sulistyarini; Purnama, Shilmu (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study aims to describe the description of the character developed by extracurricular scouting, its implementation and the obstacles experienced by extracurricular scouting at the grassroots level in shaping the character at SMPN 1 Pemangkat. The type of research taken is qualitative research with descriptive methods. Data collection techniques in this study, namely: observation, interviews and document archiving. The data sources in this study are scout coaches, school representatives, and some scout members, as well as documents or data related to extracurricular scouting. Based on the research results that: 1. There are five characters developed and in accordance with the Ministry of Education and Culture regarding Strengthening Character Education (PPK) in the 2013 curriculum, namely religious, Nationalist, Integrity, Independent, and Gotong Royong characters as indicators of successful character development. 2. The process of implementing extracurricular scout activities at the scouting level in shaping the character of members is felt to be very good and fits the character at SMPN 1 Pemangkat, although in its implementation in 2020 it could not be implemented due to the covid-19 virus pandemic. 3. The obstacles felt by extracurricular scouts when shaping character at SMPN 1 Pemangkat are in the form of funding which is still lacking to carry out existing activities and cannot carry out activities in 2020 as usual due to the covid-19 virus. However, with the scout coach's policy this can be overcome.